Some Recruitment Aspects of Population Photoscreening of Amblyogenic Factors at Children Younger One Year - Miroslav Dostálek; Jana Benešová (Acta Medica, 2002)
The aim of the study was to evaluate the keystone role of paediatric general practitioners (PGPs) in our system of photoscreening of amblyogenic factors at children younger one year. The parental involvement on the participation of their children at photoscreening was also analysed. From June 2000 to February 2001 we have performed 780 photoscreening tests of children aged from 3 months to 31 months (mean age 9.7 months). The photoscreening test was voluntary. Parents was invited to visit screening center by PGP’s recommendation and by offering the Invitation/information brochure. The brochure was distributed by 56 paediatric general practitioners during obligatory examinations at 5., 8. resp. 12. month of age from June to November 2000. Based on the questionnaire (return rate 89 %) we documented following data: the number of children of particular age in the care of PGPs was 2060, 1458 Invitation/information brochures was distributed by PGPs. PGPs attended for more children at particular age distributed relatively less number of brochures if compared to PGPs with lower number of relative children. The willingness to the photoscreening programe participance of parents of children belonging to PGPs attended our educational seminary exhibited independence on distance between PGP office and our department in the strong contrast to families belonging with PGPs not participating on educational programme. Our further effort on elevating the percentage of children population participation on screening must be focused on education of PGP with large number of children at particular age and on ensuring the issuing of brochures or other forms of invitation at PGPs’ offices.